Characterization of Periodic Micro-/Nano-Patterns for Wear Minimization of Electrical Contacts - Daniel, C; Mucklich, F; Mueller, J; Rehbein, P; Haas, V (Praktische Metallographie, 2003)
The importance of electrical connectors as well as reliability demands are constantly increasing, for example in the automobile industry. Electrical connectors are subject to high temperature changes and intense vibrations. As a consequence, contact surfaces that are not coated with noble metals but more reactive materials like tin are exposed to fretting corrosion, which can lead to system failures. A bronze-tin compound with hot tin dipped surface layers is a widely used material for contacts. Using interfering beams of a high-power Nd:YAG-Laser it is possible to pattern the microstructure periodically in order to optimize the contact behaviour under the impact of wear due to oscillating sliding action. The effect of the patterning is both an altered topography and a localized growth of intermetallic phases (Cu3Sn, Cu6Sn5) in the interface region. The resulting composite effect is based on the combination of soft, connecting and hard, wear-resistant phases. The patterned surfaces reveal an increased wear-resistivity, as tests using a special tribometer have shown. The surface as well as crosssections have been analyzed with optical and electron microscopy, white light interferometry, energy-dispersive X-ray analysis, X-ray diffraction, atomic force microscopy and nanoindentation.